Shelley Duvall's Faerie tale theatre. Tales from Hans Christian Andersen [videorecording (DVD)] - Duvall, Shelley, 1949-; Remick, Lee; Arkin, Alan; Carney, Art, 1918-2003; Olmos, Edward James; Fisher, Carrie; Jagger, Mick; Gilbert, Melissa, 1964-; Kerwin, Lance, 1960-; Shawn, Dick; Ferrell, Conchata; Andersen, H. C. (Hans Christian), 1805-1875 (Faerie tale theatre., 2009)
The Emperor's new clothes: con-artists who fool a vain and ruthless Emperor into believing that they can create the most exquisite of clothes that are invisible to those who are foolish or unworthy ; The nightingale: The Emperor of Cathay lives in a porcelain palace with his courtiers and riches, but completely cut off from any real people. When he hears about a magical bird called the nightingale and it's exquisite song, he demands an audience with it ; The Snow Queen: Gerda and Kay enter the frozen land of the Snow Queen to learn some much-needed lessons about love and friendship ; Thumbelina: A lonely char-woman is given a magical barley seed, which sprouts into a lovely flower. When the flower opens, out pops.